HETEROSIS IN LONG GRAINS AROMATIC RICES FOR YIELD AND QUALITY COMPONENTS - Singh, R. K.; Singh, OMKAR; PRASAD, B. K (Annals of Agricultural Research, 2014)
Two CMS lines, IR 68888A and IR68891 A were crossed with six long grains (6.63 to 7.73 mm) aromatic rice varieties and resultant twelve hybrids were evaluated with better parent and standard check, Pusa Basmati-1 for different yield and quality characters. Out of 12, four hybrids exhibited significant negative standard heterosis for days to maturity, whereas out of which one hybrid, IR6888A x PB-5-14-50-1 also showed significant negative standard heterosis for plant height. The heterobeltiosis and standard heterosis for grain yield per plant in hybrids ranged from 11.72 to 89.29% and 18.48 to 104.7%, respectively. Six hybrids exhibited higher degree of heterrobeltiosis and standard heterosis for grain yield. Overall three hybrids viz., IR68888AxPB-6-12-24-4, IR68888AxPB- 5-14-50-1 and IR68888 Ax Hawn Kikwani in the present study were identified superior over standard check for most of the yield and quality characters whereas two hybrids, IR68888xAPB-6-12-24-4 and IR68891AxPB-8-48-59-2 showed high heterosis as well as high outcrossing potential which can be exploited further in hybrid rice breeding programme.